1999
DOI: 10.1111/j.1469-445x.1999.01814.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relaxant Effects of Parathyroid Hormone(1‐34) and Parathyroid Hormone‐Related Protein(1‐34) on Ovine Reticulo‐Ruminal Smooth Muscle in Vivo

Abstract: summaryThe motility of the reticulo-rumen has been measured in trained, conscious sheep using inflated balloons temporarily introduced to selected regions of that forestomach. The frequency and amplitude of the contractions of the reticulum and both the A and B waves of contraction of the rumen were measured under the same conditions before, during and after the administration of an i.v. bolus of either parathyroid hormone (PTH(1-34)) or PTH-related protein (PTHrP(1-34)) followed by its i.v. infusion. These tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Therefore, a greater proportion of the EXP diet had a smaller particle size due to the zeolite A compared with the CON diet. In sheep, PTH has been shown to have relaxing effects on the reticulo-rumen smooth muscle, resulting in decreased ruminal contractions (Care et al, 1999). Although we did not measure blood PTH concentrations in the current study, it is plausible that the EXP-fed cows had increased circulating PTH compared with the CON-fed cows, resulting in slight differences in rumination rates.…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, a greater proportion of the EXP diet had a smaller particle size due to the zeolite A compared with the CON diet. In sheep, PTH has been shown to have relaxing effects on the reticulo-rumen smooth muscle, resulting in decreased ruminal contractions (Care et al, 1999). Although we did not measure blood PTH concentrations in the current study, it is plausible that the EXP-fed cows had increased circulating PTH compared with the CON-fed cows, resulting in slight differences in rumination rates.…”
Section: Discussionmentioning
confidence: 80%
“…These diseases included ketosis, retained placenta, milk fever, mastitis and metritis. Other studies also reported an association of ketosis, hypocalcaemia and milk fever with DA (Massey et al, 1993;Oikawa et al, 1997;Care et al, 1999). Duffield & Bagg (2002) also added that herds with ketosis in early lactation cows were at risk of increased incidence of DA (>8%) and increased herd removals in the first 60 DIM (<8%).…”
Section: Discussionmentioning
confidence: 93%
“…This is the first report describing such a severe transient hypotension after once-weekly injection of teriparatide. The mechanism of hypotension after injection of teriparatide was generally believed due to the vasodilating action through the vascular smooth muscle relaxant activity, accompanied by pulse increase (11,12). Hypotension has multiple possible causes, and hypotensive agents such as Ca 2 antagonist reduce vascular smooth muscle tone with increase of vessel diameter and decrease of the blood pressure (13).…”
Section: Discussionmentioning
confidence: 99%